Práticas de gerenciamento de programas aplicadas a projetos de agricultura de precisão - Siqueira, Ricardo de Fayetti (2020)
The challenge of supplying the world's populations with good quality food is a huge challenge in the face of rapid population growth. However, the challenge is enormous in the face of rapid population growth. In this context, Precision Agriculture emerges as a decisive factor to enable the increase in crop productivity. In the course of the research, we identified that the projects that involve the implementation of Precision Agriculture are a reality, however the management of these projects has not yet consolidated its own paradigm. This time, we aim with this research to propose program management practices to be applied to Precision Agriculture projects. In order to achieve this objective, we will mainly develop exploratory, qualitative research, based on semi-structured interviews. This study is effectively divided into three parts. First, we conducted a systematic review of the literature to identify research relevant to the topic and, therefore, find study opportunities. The second phase involved conducting the interviews, thus ending the data collection. Right after this step, we identified the project management practices cited, in order to compare the empirical data with the project management procedures, establishing a relationship of how the program management practices could improve the performance of agricultural precision projects. The results show that the precision agriculture projects comprise a program with four projects 1) soil fertility, 2) machinery and equipment, 3) information technology and 4) people development. The most observed areas in the projects were schedule and quality. Strategy alignment and benefit management were the most frequent on the program management side. It was evidenced that there is little formality in the processes; however the interviewees showed that they are aware that the establishment of this brings benefits to the company. An important finding was that the precision agriculture program is managed as a single large project without the use of program management techniques that make it impossible to obtain the maximum synergy between them. Thus, this study contributes from the moment that it establishes that the use of program management techniques brings competitive advantages to the organization.